Economic value of business strategy: The case of Cantonal Agricultural Center of Puriscal, Costa Rica - Céspedes Arias, Diego Armando (2024)
The Cantonal Agricultural Center of Puriscal (CACP) promotes local participation and improves the agricultural, forestry and natural resource conservation sectors. This study focused on designing a strategic plan to improve competitiveness and contribute to rural development over a five-year horizon in the CACP. The Internal Factor Evaluation Matrix (IFE), the External Factor Evaluation Matrix (EFE), the SWOT Matrix, the Analytic Hierarchy Process (AHP), the Balanced Scorecard (BSC), the Capital Asset Pricing Model (CAPM), the financial analysis of the income statements and the Net Present Value (NPV) were implemented. The main strategy focused on the commercialization of diversified agricultural and forestry products and services, with added value, oriented to the national and institutional market. The results indicated substantial improvements in financial and operational sustainability through the application of the proposed strategies.